PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH BERBASIS SUSTAINABLE LIVELIHOODS DI KABUPATEN BARRU - Maharani, Dian Putri; Mahsyar, Abdul; Akbar, Muhammad Randhy (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThe purpose of this study is to determine the application of the Sustainable Livelihood approach in maintaining the sustainability of MSMEs in Barru Regency. This research uses a descriptive qualitative research type. Data collection techniques through interviews, documents and direct observation. The data analysis technique uses "content analysis" through data reduction, data presentation and drawing conclusions. While the validation of the data using triangulation in-depth interview techniques, observation, and document review. The results of this study found that the application of a sustainable livelihoods approach to minimize risks that occur local governments have work programs run by the Cooperatives, SMEs and Trade Offices, especially in the MSME work program, namely by conducting MSME Organizational Development, Conducting Training, and Facilitating Financing Sources.Keywords: Sustainable Livelihood, Micro Small and Medium Enterprises.